Brain response during the M170 time interval is sensitive to socially relevant information. (November 2015) - Arviv, Oshrit; Goldstein, Abraham; Weeting, Janine C.; Becker, Eni S.; Lange, Wolf-Gero; Gilboa-Schechtman, Eva
Abstract: Deciphering the social meaning of facial displays is a highly complex neurological process. The M170, an event related field component of MEG recording, like its EEG counterpart N170, was repeatedly shown to be associated with structural encoding of faces. However, the scope of information encoded during the M170 time window is still being debated. We investigated the neuronal origin of facial processing of integrated social rank cues (SRCs) and emotional facial expressions (EFEs) during the M170 time interval. Participants viewed integrated facial displays of emotion (happy, angry, neutral) and SRCs (indicated by upward, downward, or straight head tilts). We found that the activity during the M170 time window is sensitive to both EFEs and SRCs. Specifically, highly prominent activation was observed in response to SRC connoting dominance as compared to submissive or egalitarian head cues. Interestingly, the processing of EFEs and SRCs appeared to rely on different circuitry. Our findings suggest that vertical head tilts are processed not only for their sheer structural variance, but as social information. Exploring the temporal unfolding and brain localization of non-verbal cues processing may assist in understanding the functioning of the social rank biobehavioral system. Highlights: Event-related magnetic fields for facial expressions and head postures were recorded. Activity at the time of M170 was sensitive to emotional and social-rank information. Head posture displaying dominance evoked greatest activation. We suggest that posture is interpreted as a social cue by ∼170 ms. Processing of social rank and emotion around the M170 rely on different circuitry.